A construção do campo pictórico: acúmulos e contraposições - Tombini, Cleandro Stevão (2014)
This research is based on a plastic practice, with the objective of construct a pictorial field through the operative concepts of accumulations and contrapositions. In its development, articulated plastic practice, based on notes made in diary of notes, with the theory, history and art criticism, and written in visual poetics. This research is established to investigate the principles that condition the instauration of my works. Thus, I begin to reflect the working documents, analyze the origin and formation of accumulations of pictorial material and its relationship with the experimental deviations, what and how the simulations and the real three-dimensional elements are opposed to the picture, coming to strategies, in which I investigate how the procedures of appropriation, collage, fusion of elements are used for work s construction. Still, do an analysis on my works, making comparisons with my previous productions, and the work of Iberê Camargo, Nuno Ramos, Leda Catunda, plus other artists with whom my work dialogues, in order to understand the developments of some procedures and my expressive intention. I conclude this study by answering the questions about the relationship and influences between painting and three-dimensional elements, and pointing possible ways to continuation of this work.